Internalisasi Nilai-Nilai Islam Melalui Bimbingan Konseling Multikultural dalam Pantang Larang - Patmawati, Patmawati; Kusumayanti, Fitri; Wafiq, Wafiq; Adiansyah, Adiansyah (Counseling As Syamil Jurnal Ilmiah Bimbingan Konseling Islam, 2024)
Write This study aims to uncover the internalization of Islamic values through the guidance of multicultural counseling in taboos. The formulation of the research problem is: how to uncover the internalization of Islamic values through multicultural counseling guidance in taboo. This research is a qualitative descriptive research, where the data is obtained through field research because the object of study is socio-cultural which is devoted to taboo collection. The steps taken are to record or document taboos that are still remembered and practiced by the community, classify taboos that contain Islamic values and interpret taboos in accordance with Islamic values which include aqidah, sharia and morals. The results of the study show that the internalization of the value of aqidah through the guidance of multicultural counseling in taboos includes all taboos, both explicit and implicit, all of which boil down to the relationship with the Creator, as seen in the taboo of burning the remaining rice stalks or rapun, the taboo of wandering around during maghrib, and the taboo of stepping over the Qur'an. The internalization of sharia values through multicultural counseling in taboos, which is a rule that builds human relationships with other humans and the universe, can be seen in the prohibition that wood must not be damaged, animals must not be killed, and fathers-to-be must not kill animals. Internalization of moral values through the guidance of multicultural counseling in taboos, seen in taboos, it is not allowed to eat while lying down later to become lazy, it is not allowed to eat messy later when the rice is crying, and it is forbidden to hit with a broom. As a result, taboos have become a culture in society as a character formation for individuals from generation to generation through telling and example.